1981
DOI: 10.1084/jem.154.5.1652
|View full text |Cite
|
Sign up to set email alerts
|

Murine syngeneic mixed lymphocyte response. I. Target antigens are self Ia molecules

Abstract: A system has been described that produces a murine syngeneic mixed lymphocyte response (MLR) comparable in magnitude to an allogeneic MLR. The responder cells in these cultures exhibit the classic immunologic characteristics of both memory and specificity. Studies using radiation-induced bone marrow chimeras of F(1) {arrow} parent type indicated that, similar to many other T cell-mediated immune responses, the response of the T lymphocytes in the syngeneic MLR was major histocompatibility complex-restricted an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

1983
1983
1994
1994

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(33 citation statements)
references
References 42 publications
2
30
1
Order By: Relevance
“…Note that Table I also shows an increase of intraceilular H-2K-positive lymphocytes for untreated cells cultured over 3 d. This phenomenon might have been the consequence of syngeneic stimulation under in vitro culture conditions as reported for murine spleen lymphocytes (15,16).…”
Section: Internalization Does Not Depend Upon Cross-linking Of the Mhsupporting
confidence: 60%
“…Note that Table I also shows an increase of intraceilular H-2K-positive lymphocytes for untreated cells cultured over 3 d. This phenomenon might have been the consequence of syngeneic stimulation under in vitro culture conditions as reported for murine spleen lymphocytes (15,16).…”
Section: Internalization Does Not Depend Upon Cross-linking Of the Mhsupporting
confidence: 60%
“…Since peripheral T cells are known to have been se lected for their low affinity for self-MHC but show high cross-reactivity to alloantigens [30][31][32], it was concluded that there exist disturbances in the T cell repertoire in aged mice. The loss of alloreactivity of aged T cells should naturally coincide with the de creased auto-MLR, as the former reflects the MHC restriction specificities of T cells having low affinity for self-MHC [33,34], In order to learn whether such age-dependent changes in the alio-and autoreactivity of T cells are inherent to the stem cells from which T cells differen tiate, we performed experiments with bone marrow chimeras. The essential findings were (1) that T cells from old bone marrow-young host chiemeras be haved like young T cells in both alio-and autoreactiv ity, and (2) that T cells from young -old chimeras re sponded to alio-and autostimulators in a pattern very similar to that of old T cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, male NOD mice display a lower spontaneous incidence of overt diabetes than females, revealing a mechanism, presumably via suppressor T cells [25], which prevents the progression of disease once insulitis is present. This resistance of male NOD mice to overt diabetes is linked to androgens [41] and results from suppressive mechanisms that can be abrogated in adults by cyclophosphamide [42][43][44], In our study, the effects induced by neonatal injections of CsA were sufficient to overcome all the safety devices which are blocked up in male NOD, Neonatal injections of CsA depressed the SMLR, which is a T cell response to self MHC class II molecules generating suppressor cells [18][19][20][21][22][23][24][25] and which is already decreased in NOD mice compared with other strains [25], Taken together, these data suggest that the neonatal CsA injections have produced a deficiency of the suppressive mechanisms involved in the resistance of male NOD mice. The time of beginning CsA administration could have been critical for enhancement of the disease.…”
Section: Discussionmentioning
confidence: 86%
“…The possible mechanisms underlying the clinical effects were investigated by analysing the phenotype of thymocyte and splenocyte subsets. Lymphocyte functions were also evaluated by mitogenesis induced by concanavalin A (Con A), or by xenogeneic insulin-producing cell extracts, or during the syngeneic mixed lymphocyte reaction which is a T cell response to self MHC class II molecules generating suppressor cells [18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%